Isoproterenol-Induced Cardiomyopathy Recovery Intervention: Amlexanox and Forskolin Enhances the Resolution of Catecholamine Stress-Induced Maladaptive Myocardial Remodeling - Adzika, Gabriel Komla; Hou, Hongjian; Adekunle, Adebayo Oluwafemi; Rizvi, Ruqayya; Adu-Amankwaah, Joseph; Shang, Wenkang; Li, Kexue; Deng, Qi-Ming; Mprah, Richard; Ndzie Noah, Marie Louise; Sun, Hong (Frontiers in Cardiovascular Medicine, 2021)
Abstract The increasing incidence of stress-induced cardiomyopathy is due to the complexities of our modern-day lives, which constantly elicit stress responses. Herein, we aimed to explore the therapeutic potential of Amlexanox and Forskolin in promoting the recovery from stress-induced cardiomyopathy. Isoproterenol-induced cardiomyopathy (ICM) models were made, and the following treatment interventions were administered: 5% v/v DMSO as a placebo, Amlexanox (2.5mg/100g/day) treatment, Forskolin (0.5mg/100g/day), and Amlexanox and Forskolin combination, at their respective aforementioned dosages. The effects of Amlexanox and Forskolin treatment on ICM models were assessed by electrocardiography and echocardiography. Also, using histological analysis and ELISA, their impact on myocardial architecture and inflammation were ascertained. ICM mice had excessive myocardial fibrosis, hypertrophy, and aggravated LVSDs which were accompanied by massive CD86+ inflammatory cells infiltration. Amlexanox treatment attenuated the myocardial hypertrophy, fibrosis, and inflammation and also slightly improved systolic functions. Meanwhile, forskolin treatment resulted in arrhythmias but significantly enhanced the resolution of myocardial fibrosis and inflammation. Intriguingly, amlexanox and forskolin combination demonstrated the most potency at promoting the recovery of the ICM from LVSD by attenuating maladaptive myocardial hypertrophy, fibrosis, and inflammatory responses. Our findings highlight the Amlexanox and Forskolin combination as a potential therapeutic intervention for enhancing cardiac function recovery from stress-induced cardiomyopathy by enhancing the resolution of maladaptive cardiac remodeling.